PENDAMPINGAN KAUM MUDA DALAM RANGKA MEWUJUDKAN SUSTAINABLE TOURISM DI DESA WISATA PURWOSARI, GIRIMULYO, KULON PROGO - Kurniawati, Lucia; Utari, Bertha Rivieda Diah; Dewi, Ike Janita; Laksono, Ferrynela Purbo; Wijayanti, Lucia Wiwid; Nugroho, Geraldus Willem Listyanto; Nugraheni, Yemima Septi; Cintyalaras, Agatha (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Youth assistance in order to realize Sustainable Tourism in Purwosari Tourism Village, Girimulyo, Kulon Progo is carried out to support the realization of sustainable tourism in Purwosari Tourism Village as mandated by the Yogyakarta Special Region Tourism Office that tourism activities in all areas of the Yogyakarta Special Region must be sustainability-oriented. This assistance is carried out in three stages, namely the preparation stage, the implementation stage, and the evaluation stage. All stages of activities will be carried out from May to August 2023. Training participants come from various generations and fields so that all parts of the community get experiences and lessons that are expected to spread to other communities. During the activity participants are active in interacting and communicating.